PENGARUH pH DAN ION ASING TERHADAP KINERJA ELEKTRODA SELEKTIF ION (ESI) TIMBAL (II) TIPE KAWAT BERBASIS PIROPILIT TERLAPIS UNTUK MENENTUKAN KANDUNGAN TIMBAL DALAM KOSMETIK - Rosemiyani, Ika; Fardiyah, Qonitah; Rumhayati, Barlah (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
ABSTRACT Lead (II) Ion Selective Electrode (ISE) based on pyrophyllite as ionofor has been developed, previously. The electrode had Polyvinilchloride (PVC) as polymer matrix and Dioctylpthalate (DOP) as plasticizer. It showed a good Nernstian slope of 29.33 mV/decade, a lead linear range concentration between 10-1- 10-5 M, and detection limit of 8.054 x10-6 M  (equal with 1.669 ppm of lead). By using the electrode, the objectives of this research were to investigate the effect of pH and interfering ions to the performance of the Lead (II) ISE based pyrophyllite coated wire type. The effects of pH was determined by measuring potential response of lead solution buffered by acetate solution at pH 3-7. The selective coefficients (kij) were determined using the mix solution methode  at  10-3 M of interfering ion. The result showed that the Lead (II) ISE based pyrophyllite coated wire type could be used optimally at  pH 5. The Lead (II) ISE based pyrophyllite coated wire type showed a good selectivity for interfering ions (Na+, Hg2+, dan Cr3+) and showed no interference to the performance of the Lead (II) ISE based pyrophyllite coated wire type with selectivity order of Pb2+> Hg2+> Cr3+> Na+. The Lead (II) ISE based pyrophyllite coated wire type could be applied for determination lead in cosmetic samples, with precision of 95.42% and accuracy of 96.49%. Based on the statistical t test with 5% confidence limit, the potentiometric method and Atomic Absorption Spectrophotometry method had no significant differences. This shows that the Lead (II) ISE based pyrophyllite coated wire type can be used to the determination of lead in cosmetic samples. Key words: coefficient of Selectivity, ISE lead (II), pH, pyrophyllite